THE BANGLADESHI EMPLOYMENT SECTOR: EMPLOYER PERSPECTIVES CONCERNING ENGLISH PROFICIENCY - Khan, Rubina; Chaudhury, Tazin Aziz (Universitas Pendidikan Indonesia, 2012)
Abstract: This paper presents a brief summary of a study which was carried out to investigate how employers representing major employment sectors in the Bangladeshi Industry view the skills and English proficiency level of the current employees. Opinions were also solicited on what skills are required for fresh recruits. Semi-structured interviews were conducted with 30 employers representing the major employment sectors in Bangladeshi Industry. Results revealed the importance of English as an indispensible means of communication in the Bangladeshi corporate sector and showed that the business enterprises use extensive amounts of English. It also highlighted that the existent English proficiency of the employees was far below the required proficiency level. Recommendations were made to address the gap and prepare the youth to meet the demands of the global market. Keywords: English proficiency, competency, employability skills, global literacy skills Â